Confronting Rouanet’s Colonial Gaze: A Critical Reading - Hicham CHAMI (Turath, 2023)
The ethnographic study of Maghrebi music culture is rooted in the colonialist discourse permeating the literature produced during (and precedent to) the period known as the “Scramble for Africa” (1884-1914). The superior/inferior trope endemic to this discourse sets European culture against local praxis, marginalizing and (mis)interpreting it from the perspective of the mission civilisatrice (“civilizing mission”) in progress in the region. My reading of Jules Rouanet’s text on Maghrebi, and specifically Moroccan, musics in the Encyclopédie de la Musique et Dictionnaire du Conservatoire uncovers problematic ideological and semantic aspects in his account while contextualizing his colonialist narrative within the prevalent corpus of Eurocentric literature. Identifying these contested presumptions and interpretations underscores the imperative for current ethnographers to not only challenge colonialist literature but reassess and ultimately decolonize “Orientalist scholarship” (cf. Laâbi, 2016, p. 67). A concurrent task interrogates the evolving standards within the disciplines of Ethnomusicology and Anthropology concerning Indigenous research which acknowledge native voices as the authoritative source of knowledge in the field setting as well as the Academy (cf. Semali & Kincheloe, 1999; Tuhiwai Smith, 2021) overturning the hegemonic Eurocentric milieu of the colonial era while owning past inaccuracies and injustices.